2020
DOI: 10.33689/spormetre.579293
|View full text |Cite
|
Sign up to set email alerts
|

İlk Ve Aci̇l Yardim Önli̇sans Programi Öğrenci̇ Ve Mezunlarinin Spora Yöneli̇k Tutumlarinin Değerlendi̇ri̇lmesi̇

Abstract: Öz: Hastane öncesi acil sağlık hizmetlerinde acil tıbbi müdahale yetkisi olan ve bu yetkiyi hastaneye ulaşıncaya kadar devam ettiren meslek mensupları "İlk ve Acil Yardım Teknikeri" olarak tanımlanmaktadır. Sağlık Bakanlığı'nın 26 Mart 2009 tarihli "Ambulans ve Acil Bakım Teknikerleri ile Acil Tıp Teknisyenlerinin Çalışma Usul ve Esaslarına Dair Tebliği"ne göre, ilk ve acil yardım teknikerlerinin tıbbi görev, yetki ve sorumlukları içerisinde fiziksel kondüsyon gerektiren "endotrakeal entübasyon, kardiyopulmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…When the effect of the participants' regular sports on the level of attitude towards the physical education lesson, a clear variance was found in favor of the students who regularly do sports. When the literature was examined (Kangalgil et al, 2004;Güllü 2007;Çelik et al, 2018;Hünük 2006;Singh and Devi, 2013;Özdinç, 2005;Sarı and Taylan, 2019;Cox et al 2008;Chung and Philips, 2002;Keskin, 2015), it was concluded that the attitudes of individuals who regularly exercise towards physical education lesson are higher than those who did not. These results support the result of our study.…”
Section: Discussion Conclusion and Recommendationmentioning
confidence: 99%
“…When the effect of the participants' regular sports on the level of attitude towards the physical education lesson, a clear variance was found in favor of the students who regularly do sports. When the literature was examined (Kangalgil et al, 2004;Güllü 2007;Çelik et al, 2018;Hünük 2006;Singh and Devi, 2013;Özdinç, 2005;Sarı and Taylan, 2019;Cox et al 2008;Chung and Philips, 2002;Keskin, 2015), it was concluded that the attitudes of individuals who regularly exercise towards physical education lesson are higher than those who did not. These results support the result of our study.…”
Section: Discussion Conclusion and Recommendationmentioning
confidence: 99%